Perbandingan Motivasi Kerja Ruang Rawat Inap Dan Ruang Operasi Dalam Pelaksanaan Pendokumentasian Di Rumah Sakit Murni Teguh Sudirman Jakarta - Siahaan, Risma Tio; Silaen, Harsudianto (Indonesian Trust Nursing Journal, 2024)
Nursing care documentation is a documentation that contains complete, real, and recorded data, not only about the level of client pain, but also the type or type, quality, and quantity of health services in meeting needs. Nursing care that is not documented accurately and completely will make it difficult to prove that the nursing care has been carried out correctly. The objective of this study is to analyze the comparison of work motivation in inpatient and operating unit in the implementation of documentation. The research design uses a cross-sectional approach in quantitative research. The sample in this study was 20 respondents using purposive sampling. Data was analyzed using Independent paired T-Test. The results of the statistical test between the motivation of inpatient room nurses and the motivation of operating room nurses in the implementation of nursing documentation using the Independent t-test statistical test showed that there was a comparison between the motivation of inpatient room nurses and operating room nurses with a p value <005, namely 0.010. It is concluded that therewas a comparison between the nurses’s work motivation in inpatient and operating unit at Murni Teguh Sudirman Hospital, Jakarta.